This is monstropolis! - Jessup, Harley; Sheehy, Sterling (New York : Disney Press, 2013)
This oversized board book with flaps illustrates the world of Monstropolis. The book features illustrations by Pixar talent Harley Jessup, and more than seventy flaps throughout the book that reveal extra surprises.
At head of title: Disney-Pixar Monster University
On board pages.
Keywords: Children's stories